2010
DOI: 10.1371/journal.pone.0014359
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Heteroplasmic Mitochondrial DNA in Single Mitochondria

Abstract: BackgroundMitochondrial DNA (mtDNA) genome mutations can lead to energy and respiratory-related disorders like myoclonic epilepsy with ragged red fiber disease (MERRF), mitochondrial myopathy, encephalopathy, lactic acidosis and stroke (MELAS) syndrome, and Leber's hereditary optic neuropathy (LHON). It is not well understood what effect the distribution of mutated mtDNA throughout the mitochondrial matrix has on the development of mitochondrial-based disorders. Insight into this complex sub-cellular heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…For example, elevated oxidative stress in chronic peritoneal dialysis patients may lead to alterations in the mtDNA copy number in peripheral leukocytes [33]. In our current study, the mtSNPs listed in Table 3 were homoplasmic, as revealed by sequencing chromatograms (data not shown) [58][60]. However, we cannot exclude the possibility that a minor fraction of heteroplasmic mutations, below the level of sensitivity of the sequencing method that we used, may be present.…”
Section: Discussionmentioning
confidence: 55%
“…For example, elevated oxidative stress in chronic peritoneal dialysis patients may lead to alterations in the mtDNA copy number in peripheral leukocytes [33]. In our current study, the mtSNPs listed in Table 3 were homoplasmic, as revealed by sequencing chromatograms (data not shown) [58][60]. However, we cannot exclude the possibility that a minor fraction of heteroplasmic mutations, below the level of sensitivity of the sequencing method that we used, may be present.…”
Section: Discussionmentioning
confidence: 55%
“…While others have measured genetic variation of mtDNA isolated from single mitochondrion, these studies were limited to specific regions of the mtDNA, focused specifically on deletions, or measured a single mitochondrion isolated from a complex mixture of cell types (Cavelier et al, 2000; Reiner et al, 2010; Poe III et al, 2010)). This precludes assessment of total mutational burden across the entire genome for all genomes present.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there was little insight into the degree of divergence of genes at the level of the individual cell, a process termed as heteroplasmy. Heteroplasmy has been documented in various metazoan groups [18][25] and the kinetoplastid protist Trypanosoma cruzi [26] but not in ciliated protists. Therefore, it is not possible to conclusively determine whether the observed intra-specific divergence of mitochondrial genes in ciliates is genuine or the result of intra- individual genetic variation.…”
Section: Introductionmentioning
confidence: 99%